Reduced pulmonary arterial compliance predicts poor short-term outcome in children with pulmonary arterial hypertension independent of pulmonary vascular resistance - Gouwy, Eva; Ploegstra, Mark-Jan; Haarman, Meindina G.; Roofthooft, Marcus T. R.; Berger, Rolf M. F.; Douwes, Johannes M. (Frontiers in Cardiovascular Medicine, 2025)
Background and study aimPulmonary arterial hypertension (PAH) is a progressive pulmonary vascular disease with pulmonary vascular remodelling leading to an increased pulmonary vascular resistance (PVRi) and decreased pulmonary arterial compliance (PACi). It is debated whether PACi provides prognostic information additional to PVRi and whether the relationship between PVRi and PACi, expressed as their product resistance-compliance-time (RC-time), is constant. The aim of this study is to investigate the relationship between PVRi and PACi and to determine the prognostic value of PACi in addition to PVRi in newly diagnosed children with idiopathic or heritable pulmonary arterial hypertension (IPAH/HPAH).MethodsIn this retrospective analysis of prospectively collected data, 62 consecutive children with IPAH/HPAH that had a diagnostic heart catheterization between 1993 and 2021 at the University Medical Center Groningen were included. The relationship between PACi and PVRi was assessed using curve estimation and linear regression analysis, the relationship of PACi with disease severity was assessed using Spearman correlation and the relationship of PACi with outcome was assessed using cox regression analysis.ResultsA power curve with formula PACi = 5.13 · PVRi−0.66 was the best fit for the relationship between PACi and PVRi, and RC-time varied between patients. PVRi and PACi both correlated with markers of disease severity and transplant-free survival. PACi was associated with 1-year transplant-free survival independent of mean pulmonary arterial pressure (mPAP) (p = 0.031), PVRi (p = 0.029), and age, sex and treatment intensity (p = 0.019).ConclusionThe relationship between PACi and PVRi is not constant. PACi is associated with disease severity and predicts short term outcome in children with IPAH/HPAH independent of PVRi and mPAP. Therefore, PACi is of additional prognostic value to PVRi, especially for short term prediction.